Ask a question
0 0

Simplify (u^-6)^2. Write your answer without using negative exponents.

the -6 is smaller and above the u. the 2 is outside the parentheses and smaller. 


Tutors, please sign in to answer this question.

2 Answers

Given that the expression you're trying to simplify looks like this --- (u-6)2 ---  here's how I would start to tackle it. 

Expression:                       (u-6)2
Multiply the exponents:     u

Then, it's important to know that  u-1  = 1/u
When you apply that to the expression you are working with, it looks like this:

Flip expression to remove negative exponent: 1/u12

Hi Angela!

You could simply but surely "type out" the expression:

u^-1= 1/u ==> u^-6= 1/(u*u*u*u*u*u), now squaring this thing means you'll have twice as many u's ...

Since (1/u)^2= (1/u)(1/u) ==> (1/u^6)(1/u^6)= 1/(u^12)  Best wishes, ma'am :)